Confirmatory analysis of the Parenting Styles and Dimensions Questionnaire (PSDQ) short form in a portuguese sample - Martins, Cátia (2018)
An important research field in family studies relates to the role parenting practices can have on several domains of children’s development. Regarding to parenting styles, it was Baumrind’s conceptualization that was responsible for a relevant research boost in this area. She proposed a model contemplating three different styles: authoritative, authoritarian, and permissive. The aim of our study was to examine the factor structure, internal consistency and others psychometric properties of the Portuguese version of the Parenting Styles and Dimensions Questionnaire (PSDQ). The participants were 424 parents (mainly mothers, 81.2%) from Algarve (South of Portugal), that answered to PSDQ and a sociodemographic questionnaire. The instrument comprises 32 items: 12 questions regarding the authoritative style, 15 questions regarding the authoritarian style, and 5 questions regarding the permissive style. Several competing models (i.e., one and three-factorial, and another where latent variables were organized in a 1st and 2nd order factors) were tested in regards to PSDQ factor structure using confirmatory factor analysis. A fourth model, contemplating inter-correlations between item 7 and 8 was also proposed, which showed adequate fit and internal consistency. These findings support the PSDQ original structure. Implications concerning the use and contributes to social and emotional child’ adjustment are discussed.